The Wireless Officer - Westerman, Percy F. (Percy Francis), 1876-1959; Wigfull, W. Edward (William Edward), 1875-1944 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Wireless Officer" by Percy F. Westerman is a novel written in the early 20th century. This adventurous tale follows a young wireless officer named Peter Mostyn as he navigates life on the high seas, tackling challenges both at sea and on land while dealing with the dynamics of a post-war maritime world. The narrative centers around Peter's newfound position aboard the S.S. "West Barbican", where he is eager to prove his worth after a lengthy period without a ship. The opening of the story introduces Peter Mostyn, who joyfully receives news of his appointment to the S.S. "West Barbican" after being out of work for six months due to a downturn in British shipping. We learn about his excited preparations, his family's maritime background, and his father, Captain Mostyn, who is managing director of the Brocklington Ironworks Company. The chapter hints at intrigue and tension, particularly with competition from a German firm as well as Peter's personal challenges. As Peter boards the ship, he meets the crew, including the gruff captain, and is concerned about the unpreparedness of his inexperienced assistants, setting the stage for future conflicts and adventures. (This is an automatically generated summary.)
Release date is 2011-10-22
Produced by Al Haines
Keywords: Sea stories; Spy stories; Telegraphers -- Juvenile fiction